PERLAKUAN AKTIVATOR DAN MASA INKUBASI TERHADAP PELAPUKAN LIMBAH JERAMI PADI - Suwastika, A.A.N.G.; Sutari, Ni Wayan Sri (Bumi Lestari; Vol 9 No 2 (2009), 2009)
The experiment was intended to study the effect of activator and incubation treatments of paddy straw decomposition on total-N and compost C/N ratio. The experiment was conducted in green house of Faculty of Agriculture Udayana University research station, Pegok Denpasar, from June to October 2007. The experiment was conducted in a randomized block design arranged in factorial pattern with three replications. Two factor were used which were activators (control, EM4, Super Degra, and R1M) and the second factor were incubation periods consisted of 4, 8, and 12 weeks. The result this experiment indicated there was a significant effect of interaction between activator and incubation period on total-N compost, but on C/N ratio was not significant interaction. The highest of total-N compost was found on 12 weeks incubation period with R1M activator (2.67 %), then decreased to EM4, Super Degra, and control treatments, with total-N content were 2.55 %, 2.34 %, and 2.00 %, respectively. Single effect of activator was significant to C/N ratio. The highest C/N ratio was found on control treatment (39.07) and decreased on EM4, R1M, and Super Degra treatments, with compost C/N ratio were 34.40, 33.90, and 33.62. Single effect of incubation period was significant to compost C/N ratio. The lowest C/N ratio was found on 12 weeks incubation period (14.24) and increased on 8 weeks and 4 weeks incubation period, with the C/N ratio were 30.42 and 61.07, respectively.
Keywords: paddy straw, compost, activator, incubation period